Development of an evidence-based regimen of prednisolone to treat giant cell arteritis – the Norwich regimen. Issue 1 (1st February 2019) - Mukhtyar, Chetan; Cate, Heidi; Graham, Conor; Merry, Peter; Mills, Karen; Misra, Aseema; Jones, Colin
Abstract: We have reviewed the literature to form a bespoke regimen for daily oral prednisolone (DP) in GCA. Initial DP in clinical trials is 40–60 mg daily, but relapse rates are 67–92%. Cumulative prednisolone (CP) of 3.2 and 3.9 g (at 6 months) resulted in a relapse rate of 83 and 67%, respectively; and 3 and 3.9 g (at 12 months) resulted in 92 and 82% relapse, respectively. CP was 6.2–7.1 g in the first year. Mean DP was 18.8 mg at 3 months and 6.6–7.4 mg at 12 months. The duration of treatment with prednisolone for GCA was 22–26 months. The CP to achieve discontinuation was 6.5–12.1 g. Using these data, the Norwich regimen starts DP at 1 mg/kg/day of lean body mass, discontinuing over 100 weeks. For the average UK woman, initial DP is 45 mg daily, reaching 21 mg daily by 12 weeks and 6 mg daily by 52 weeks. The CP for the average UK woman would be 6.5 g at 52 weeks and 7.4 g to discontinuation.